A Time-Domain Boundary Element Method for Wave Diffraction in a Two-Layer Fluid - Ying Gou; Xin-jia Chen; Teng Bin (Journal of Applied Mathematics)
A time-domain numerical model is established based on the higher-order boundary element method (HOBEM) to simulate wave diffraction problem in a two-layer fluid of finite depth. There are two possible incident wave modes (surface-wave mode and internal-wave mode) exist in the incident wave for a prescribed frequency in a two-layer fluid. For surface-wave mode, the hydrodynamic characters of fluid particles are similar to single-layer fluid. For the internal-wave mode, through the definition of a new function respected to velocity potentials of upper and lower fluid on the interface by using matching condition, a single set of linear equations is set up to compute the time histories of wave forces and wave profiles by using a fourth-order Runge-Kutta method. An artificial damping layer is adopted both on the free surface and interface to avoid the wave reflection. Examinations of the accuracy of this time-domain algorithm are carried out for a truncated cylinder and a rectangular barge, and the results demonstrate the effectiveness of this method.